Estimation of post-adjustment correlations between observations on the basis of their topological coexistence in the network - Kwaśniak, Mieczysław (Geodesy and Cartography, 2008)
The paper presents the results of the studies on the determination of the degree of dependence between the adjusted observations, on the basis of the levels of their coexistence in a network. An approximate model is proposed making it possible to estimate that dependence without the necessity to perform the adjustment procedure. This model can be applied in the procedures of gross error detection in observations. Additionally, a supplementary algorithm to determine the coexistence levels for the observations on the grounds of the matrix of coefficients in the observation equations is presented.
Keywords: Adjusted observations; covariance matrix; observation coexistence level